Progress in animal breeding - Smith, W.H. (Kansas Agricultural Experiment Station, 2011)
The purebred livestock industry was well established in the United States 50 years ago. Breed registries were active in promoting breeds and maintaining pedigree records then. Livestock shows were well established in the early 1900’s and have continued with breeders relying on placings made in shows for guidance in livestock selection. More recently, livestock carcass class competition has been introduced and the discrimination has increased against excess external carcass fat as appraised in both live slaughter animals and their carcasses.
Keywords: Animal breeding; Carcasses; Performance traits